PENGARUH FILSAFAT PENDIDIKAN TERHADAP IMPLEMENTASI KURIKULUM MERDEKA PADA GURU DAN PESERTA DIDIK PENDIDIKAN DASAR - Apala, Hesti; Hidayat, Rahmat; Putri, Mahdatul Aini; Nurwahidin, Muhammad (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2025)
This study aims to examine the influence of educational philosophy on the implementation of the Kurikulum Merdeka among teachers and students at the elementary education level. Educational philosophy, which encompasses principles of constructivism, humanism, and progressivism, is expected to underpin the application of a flexible and student-centered curriculum. Using a literature review approach, the study finds that a deep understanding of educational philosophy enables teachers to design learning processes tailored to students' needs and characteristics, creating a more inclusive and participatory learning environment. Conversely, the main challenges in implementing the Kurikulum Merdeka lie in many teachers' lack of understanding of educational philosophy principles and the limited training provided. Therefore, the study emphasizes the importance of continuous professional development for teachers and stronger policy support from the government to ensure the successful implementation of the Kurikulum Merdeka. Thus, the proper integration of educational philosophy can enhance learning quality and support students' character and skill development.